Drinking Water Treatment Residuals to Control Phosphorus in Soils - Jonathan D. Judy; Maria L. Silveira; Sampson Agyin-Birikorang; George O'Connor; Thomas A. Obreza (EDIS)
Soils in Florida may contain excess soil phosphorus (P) resulting from fertilizer, manure or biosolids applications. Excess P in soil does not damage soil fertility but can be transported from agricultural and urban areas either dissolved in water that drains away or as particulate matter (attached to soil particles) that travels with eroding soil.  Increased P in water bodies is recognized as one of the major factors responsible for eutrophication-related decrease in water quality.  Most soils have the capacity to retain excess P. However, soils with low capacity to retain excess P are abundant in Florida.  The use of drinking-water treatment residuals (WTR) to control excess phosphorus (P) in soils with limited P adsorption capacity has been explored as a potential low-cost method by which to reduce phosphorus losses to surface waters and a discussion of these explorations is presented here. The target audience for this publication includes state agencies, like the Florida Department of Environmental Protection (FLDEP), and water management districts trying to control P pollution, and those interested in nutrient management for agricultural and environmental purposes. This 6-page fact sheet is a minor revision written by Jonathan D. Judy, Maria L. Silveira, Sampson Agyin-Birikorang, and George A. O’Connor, and published by the UF/IFAS Department of Soil and Water Sciences, June 2019.